A Regularity Criterion for the Magneto-Micropolar Fluid Equations in B˙∞, ∞−1. (27th March 2013) - Tang, Zhihao; Wang, Gang; Guan, Haiwa
Abstract : The paper is dedicated to study of the Cauchy problem for the magneto-micropolar fluid equations in three-dimensional spaces. A new logarithmically improved regularity criterion for the magneto-micropolar fluid equations is established in terms of the pressure in the homogeneous Besov space B ˙ ∞, ∞ − 1 .